KEKERASAN DALAM RUMAH TANGGA (ANALISIS FAKTA SOSIAL BERBASIS KONSELING FEMINIS TERHADAP KETIMPANGAN GENDER) - Surianti Surianti (Pusat Studi Gender dan Anak, IAIN Palu, 2018)
Domestic violence (KDRT) is the most common violence of women in Indonesia. This occurs because of gender imbalances that differentiate women's and men's roles and rights in the community that places women in a lower status than men. The privilege of men as if they make women the property of men who are entitled to be treated arbitrarily, including by violence. The counseling theory approach that is considered relevant to domestic violence cases is feminist counseling. Concepts built in feminist theory use a system perspective, meaning that the process of counseling intervention is not only to individuals but the individual environment is given the treatment to ensure the solution of the root of the problem. The ability of counselors to empower individuals/communities within the victim's environment is a skill that must be sharpened by counselors who use feminist counseling. This theory is based on the principles of the personal is political, egalitarian relationship and the valuing perspective. The three concepts that become pillars of feminist counseling become an essential indicator in determining the ability of counselor in assisting women victims of domestic violence.